Expression of the Ephrin Receptor B2 in the Embryonic Chicken Bursa of Fabricius - Weathers, Brett; Branton, Scott L.; Jacob, Roymon; Taylor Jr, Robert L.; Peebles, E. David; Pharr , G. Todd (International Journal of Poultry Science, 2015)
Chicken B-cells develop in the bursa of Fabricius. To understand the bursal microenvironment guiding B-cell development, previous studies identified ephrin (Eph) receptor B2 (EphB2) gene transcripts in the embryonic bursa. We hypothesize that the EphB2 receptors and their ligands could initiate contacts between developing B-cells and epithelial cells in the embryonic bursal follicle. To address this hypothesis, additional basic studies were conducted to determine if EphB2 is expressed in the embryonic bursa. Therefore, EphB2 gene expression was examined with reverse transcriptase-PCR and western blotting in the bursa on embryonic days (ED) 15 and 18. The RT-PCR experiments with bursal cDNA amplified transcripts from the EphB2 gene, which was confirmed by nucleotide sequencing. The anti-EphB2 antibody recognized a protein of the expected 120 kDa molecular mass and gave an acceptable signal to noise ratio on whole tissue protein western blots from the ED15 and ED18 bursa. This information can be used to design experiments for determining the cell type (s) expressing the EphB2 protein in the embryonic bursa.